2021
DOI: 10.7759/cureus.16104
|View full text |Cite
|
Sign up to set email alerts
|

A Flare of Systemic Lupus Erythematosus Disease After COVID-19 Infection: A Case of Lupus Cerebritis

Abstract: The association between coronavirus disease 19 (COVID-19) and autoimmune disease has been mounting, and literature on COVID-19-induced flare-up of systemic lupus erythematosus (SLE) disease is lacking. We describe a case of lupus cerebritis triggered by COVID-19 in a young female with SLE, who presented with fluctuated mentation, psychomotor retardation, slow speech, and intermittent choreiform movement in the upper part of the body. She had a history of COVID-19 infection three weeks back. Her serum immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…It is also noted a production of antibodies like ANA, antiphospholipid antibody, ANCA, anti CCP, Ro/SSA; which are thought to play a part in SLE exacerbation. (Gazzaruso et al, 2020;Gracia-Ramos et al, 2021;Zamani et al, 2021) In literature, this is not the only case describing this association (Khalid et al, 2021;Alharthy et al, 2020). This can explain the SLE disease aggravation after infection with Covid-19, as in our clinical case, along with severe organ involvement.…”
Section: Discussionsupporting
confidence: 52%
“…It is also noted a production of antibodies like ANA, antiphospholipid antibody, ANCA, anti CCP, Ro/SSA; which are thought to play a part in SLE exacerbation. (Gazzaruso et al, 2020;Gracia-Ramos et al, 2021;Zamani et al, 2021) In literature, this is not the only case describing this association (Khalid et al, 2021;Alharthy et al, 2020). This can explain the SLE disease aggravation after infection with Covid-19, as in our clinical case, along with severe organ involvement.…”
Section: Discussionsupporting
confidence: 52%
“…Additional symptoms and risks include severe metabolic syndrome, acute renal injury, neurological diseases, cardiovascular and thromboembolic events such as encephalopathy, seizures, and stroke [ [6] , [7] , [8] , [9] , [10] ]. A possible relationship between COVID-19 and autoimmune diseases such as SLE has also been recently documented in many case reports within the literature [ [11] , [12] , [13] ]. However, there is a lack of data and knowledge on LN in conjunction with MCTD in COVID-19 positive patients.…”
Section: Introductionmentioning
confidence: 92%
“…Data about the association between COVID-19 and SLE [45][46][47] or SSc [13,48,49] are scarce. However, there have been reports in the literature of COVID-19 shortly preceding a de novo diagnosis of SLE, presenting concomitantly, mimicking or worsening SLE manifestations, raising the possibility of SARS-CoV-2 being an autoimmunity trigger [50][51][52][53][54][55]. There are a few critical points of convergence between SLE and COVID-19 and they are: (1) type I interferons (IFNs) (which play a crucial role in the course of disease and outcomes of COVID-19, while patients with SLE have elevated circulating type I IFN or show overexpression of type I IFN genes in circulating immune cells); (2) neutrophil extracellular traps (NETs= web-like chromatin fibers with microbicidal proteins enhance inflammation and type I IFN responses in SLE, potentiate thrombosis in antiphospholipid syndrome and recent studies have suggested its key role in COVID-19); (3) complement system (dysregulation is a classic feature of SLE, and hypocomplementemia is a marker of disease activity; complement activation has been also associated with the excessive inflammatory response seen in patients with severe COVID-19); and (4) mechanistic (mammalian) target of rapamycin (mTOR-regulates T-cell and macrophage differentiation, and is thought to play a critical role in the pathogenesis of autoimmune and inflammatory diseases, such as SLE; mTOR signaling has been shown to be decreased in pDCs from COVID-19 patients, which may negatively impact the host antiviral response [56]).…”
Section: Discussionmentioning
confidence: 99%